Contemporary antiretrovirals and body-mass index: a prospective study of the RESPOND cohort consortium. Issue 11 (November 2021) - Bansi-Matharu, Loveleen; Phillips, Andrew; Oprea, Cristiana; Grabmeier-Pfistershammer, Katharina; Günthard, Huldrych F; De Wit, Stephane; Guaraldi, Giovanni; Vehreschild, Jorg J; Wit, Ferdinand; Law, Matthew; Wasmuth, Jan-Christian; Chkhartishvili, Nikoloz; et al.
Summary: Background: Weight gain effects of individual antiretroviral drugs are not fully understood. We investigated associations between a prespecified clinically significant increase (>7%) in body-mass index (BMI) and contemporary antiretroviral use. Methods: The International Cohort Consortium of Infectious Diseases (RESPOND) is a prospective, multicohort collaboration, including data from 17 well established cohorts and over 29 000 people living with HIV. People with HIV under prospective follow-up from Jan 1, 2012, and older than 18 years were eligible for inclusion. Each cohort contributed a predefined minimum number of participants related to the size of the specific cohort (with a minimum of 1000 participants). Participants were required to have CD4 cell counts and HIV viral load measurement in the 12 months before or within 3 months after baseline. For all antiretroviral drugs received at or after RESPOND entry, changes from pre-antiretroviral BMI levels (baseline) were considered at each BMI measurement during antiretroviral treatment. We used logistic regression to identify individual antiretrovirals that were associated with first occurrence of a more than 7% increase in BMI from pre-antiretroviral BMI. We adjusted analyses for time on antiretrovirals, pre-antiretroviral BMI, demographics, geographical region, CD4 cell count, viral load, smoking status, and AIDS at baseline. Results: 14 703 people were included in this study, of whom 7863 (53·5%) had a more than 7% increase in BMI. Compared with lamivudine, use of dolutegravir (odds ratio [OR] 1·27, 95% CI 1·17–1·38), raltegravir (1·37, 1·20–1·56), and tenofovir alafenamide (1·38, 1·22–1·35) was significantly associated with a more than 7% BMI increase, as was low pre-antiretroviral BMI (2·10, 1·91–2·31 for underweight vs healthy weight) and Black ethnicity (1·61, 1·47–1·76 vs White ethnicity). Higher CD4 count was associated with a reduced risk of BMI increase (0·97, 0·96–0·98 per 100 cells per μL increase). Relative to lamivudine, dolutegravir without tenofovir alafenamide (OR 1·21, 95% CI 1·19–1·32) and tenofovir alafenamide without dolutegravir (1·33, 1·15–1·53) remained independently associated with a more than 7% increase in BMI; the associations were higher when dolutegravir and tenofovir alafenamide were used concomitantly (1·79, 1·52–2·11, and 1·70, 1·44–2·01, respectively). Interpretation: Clinicians and people with HIV should be aware of associations between weight gain and use of dolutegravir, tenofovir alafenamide, and raltegravir, particularly given the potential consequences of weight gain, such as insulin resistance, dyslipidaemia, and hypertension. Funding: The CHU St Pierre Brussels HIV Cohort, The Austrian HIV Cohort Study, The Australian HIV Observational Database, The AIDS Therapy Evaluation in the Netherlands national observational HIV cohort, The EuroSIDA cohort, The Frankfurt HIV Cohort Study, The Georgian National AIDS Health Information System, The Nice HIV Cohort, The ICONA Foundation, The Modena HIV Cohort, The PISCIS Cohort Study, The Swiss HIV Cohort Study, The Swedish InfCare HIV Cohort, The Royal Free HIV Cohort Study, The San Raffaele Scientific Institute, The University Hospital Bonn HIV Cohort and The University of Cologne HIV Cohorts, ViiV Healthcare, and Gilead Sciences.